2007
DOI: 10.1016/j.ydbio.2007.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of germ cells during gonadal sex differentiation in medaka: Insights from germ cell-depleted mutant zenzai

Abstract: The proliferation of germ cells becomes sexually dimorphic during gonadal sex differentiation, although the underlying dynamics of this are not well understood in vertebrates. By tracing GFP-labeled germ cells in vivo and analyzing the germ cell-depleted mutant, zenzai, we show that the proliferation and differentiation of germ cells are regulated in a sexually dimorphic manner in the teleost fish medaka. In the undifferentiated gonads, germ cells resume proliferation by slow intermittent division (type I), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 31 publications
5
111
0
4
Order By: Relevance
“…In a similar fashion to C. carpio, Saito et al (2007) reported the sexual discernment as an early event during gonad development in Oryzias latipes that was signaled by one of two types of germ cell proliferation. Type I proliferation involved the stem cell self-renewal and produced isolated daughter cells.…”
Section: Formation Of Female Germinal Epithelium In Fishmentioning
confidence: 68%
See 3 more Smart Citations
“…In a similar fashion to C. carpio, Saito et al (2007) reported the sexual discernment as an early event during gonad development in Oryzias latipes that was signaled by one of two types of germ cell proliferation. Type I proliferation involved the stem cell self-renewal and produced isolated daughter cells.…”
Section: Formation Of Female Germinal Epithelium In Fishmentioning
confidence: 68%
“…In a fashion that is similar to that which occurs in the ovarian germinal epithelium lining the ovigerous lamellae in sexually mature females (Grier, 2000;Le Menn et al, 2007;Grier et al, 2009), and also in the differentiating ovary of Oryzias latipes (Saito et al, 2007) and C. carpio, individual oogonia divide mitotically forming a germline cyst of interconnected germ cells that synchronously enter into meiosis, becoming oocytes. ''Cysts are groups of cells that form from a single founder cell.…”
Section: The Formation Of the First Ovarian Folliclesmentioning
confidence: 77%
See 2 more Smart Citations
“…The interconnected germ cells are packaged as a cyst and surrounded by somatic cells. Following several rounds of mitosis, the cells enter meiosis to become eggs in the ovary or sperms in the testis 28, 29. Interestingly, the number of successive division rounds differs between oogenesis and spermatogenesis in medaka 20, 30.…”
Section: Early Gametogenesis − From Germline Stem Cells To Entry Of Mmentioning
confidence: 99%